Evolution Magmatism of Nagasari Volcano Dieng, Central Java, Indonesia - Dwi Fitri Yudiantoro; Intan Paramita Haty; Setia Pambudi; Elisabet Magdalena; Armala Putri; I. Takashima; M. Abdurrachman (Journal of Geoscience, Engineering, Environment, and Technology, 2022)
Nagasari Volcano, part of the Dieng volcanic complex, is one of the unique volcanoes in Central Java. Around this volcano grow eruption craters, volcanic cones, and pyroclastic flow ridges. There were several 14 eruption centers around Mount Nagasari, so it is necessary to know the development of magmatism evolution. The aims of the research to determine the evolutionary development of magmatism. The methodology used is geological mapping and petrographic analysis. The observations of rocks found in the study area include andesite lava, lapilli-tuff, fallen pyroclastic breccias, and flow pyroclastic breccias. Meanwhile, geological mapping and petrographic observations of volcanic rock samples show that the evolution of magmatism in the study area from the oldest to the youngest is basaltic magma that formed Prau Volcano in the pre-caldera period. On the other hand, magmatism in the post-caldera I period was of the type of pyroxene andesite forming the Gembol to Jimat Volcano group. In contrast, in the post-caldera II period, the hornblende-biotite andesite group formed the Dieng Kulon to Kendil group.